A STUDY OF LIVER FUNCTION TESTS DERANGEMENTS IN LEPTOSPIROSIS IN A TERTIARY HEALTH CARE CENTER IN ODISHA: A COHORT STUDY. - Nanda, Bikash Chandra; Naik, Manoranjan; Khamari, Balaram (Student's Journal of Health Research Africa, 2025)
Background A zoonotic illness that is found throughout the world is leptospirosis. For growth, leptospires need specific media and circumstances. Positive cultural shifts might occur over weeks or months. Clinical, diagnostic, and epidemiologic objectives are best served by classifications based on serologic distinctions. Objectives This study aims to determine the distribution of leptospirosis patients by identifying the correlation between clinical factors at admission and six weeks later in leptospirosis patients. Materials and Methods The study was observational and prospective. The study was conducted in Burla, Sambalpur, Odisha, India, at the Veer Surendra Sai Institute of Medical Sciences and Research (VIMSAR). The research was conducted between February 2024 and January 2025. One hundred patients in all were enrolled in the trial. Results A total of 100 IgM lepto-antibody-positive patients were enrolled and completed the 6-week follow-up. The mean age was 42.3 ± 13.8 years, with 61% males and 39% females. Fever and myalgia were present in all patients, with other common symptoms including headache (75%) and icterus (68%). Liver function parameters such as AST, ALT, bilirubin, ALP, total protein, and albumin showed significant improvement after 6 weeks (p < 0.001). These results indicate notable hepatic recovery in leptospirosis patients. Conclusion The study came to the conclusion that elevated levels of bilirubin and transaminases were the primary way that the liver was involved in leptospirosis. Patients' bilirubin, AST, and ALT levels were much lower at 6 weeks than they were at admission. Recommendation Early diagnosis and regular monitoring of liver function are essential for effective management of leptospirosis. Public health strategies should focus on awareness and timely intervention to prevent hepatic complications.